1993
DOI: 10.1007/bf01973640
|View full text |Cite
|
Sign up to set email alerts
|

Oral itraconazole plus nasal amphotericin B for prophylaxis of invasive aspergillosis in patients with hematological malignancies

Abstract: The use of oral itraconazole (200 mg daily) plus nasal amphotericin B (10 mg daily) for prophylaxis of invasive aspergillosis was evaluated in 164 patients with hematological malignancies at risk due to presence of neutropenia and/or steroid therapy. This prophylactic regimen was evaluated for a period of two years. Two hundred and ninety patients with similar characteristics who were observed over the three-year period prior to the introduction of prophylaxis served as historical control group. Environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
0
25
0
3
Order By: Relevance
“…Both trials clearly showed a marked reduction of invasive fungal infections. The largest study until now was reported by Todeschini et al, 18 who compared 164 patients with 200 mg/day itraconazole and nasal amphotericin B to a historical group of 290 patients with no antifungal prophylaxis. The rate of proven invasive aspergillosis fell from 4 to 0% (P = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Both trials clearly showed a marked reduction of invasive fungal infections. The largest study until now was reported by Todeschini et al, 18 who compared 164 patients with 200 mg/day itraconazole and nasal amphotericin B to a historical group of 290 patients with no antifungal prophylaxis. The rate of proven invasive aspergillosis fell from 4 to 0% (P = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…The median length of neutropenia was 18 days (range 5-33). Eighteen of 28 patients had AML with a median neutropenic length of 20 days (range 5-33), and 10/18 patients had ALL with a median neutropenic period of 13 days (range [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Time Framesmentioning
confidence: 99%
“…Group 3-a consisted of 37 AML patients with median length of neutropenia of 16 days (range 5-120), and 8 ALL patients with median of 17 days (range 7-40) of neutropenia. Group 3-b consisted of 23 AML patients with median neutropenia duration of 15 days (range 5-42), and 3 ALL patients with median neutropenia duration of 11 days (range [8][9][10][11][12][13][14][15][16][17][18][19][20]. In group 3-c 26 patients underwent allogeneic BMT in the hematology ward with a median neutropenic period of 15 days (range 9-26), and 168 patients underwent autologous BMT in the hematology ward with median neutropenic period of 10 days (range 7-25).…”
Section: Time Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Itraconazole capsules had activity in the treatment of invasive aspergillosis 16 and had been used as prophylaxis in high-risk patients with variable results. [17][18][19][20] However, the bioavailability of itraconazole in capsule form was unpredictable between and within patients, 21 particularly if concomitant antacids were used. A new cyclodextrin-based oral itraconazole solution had recently become available.…”
Section: Gvhdmentioning
confidence: 99%